A Study on the Suggestions and Analysis on the Education Programs in the Presidential Libraries - Han, Mi-Kyung (International Journal of Knowledge Content Development & Technology, 2011)
Presidential records are produced and collected with regard to Presidents’ performance of his duties. Presidential libraries provide the users with open reading, exhibition, education, and promotion services. To maximize utilization of Presidential records as knowledge and information contents, it is most important to build educational programs as active services available. In this context, this study conducts investigation of the current status of education programs of Korea and US Presidential libraries. And this study also examines and analyzes distinguishing programs of 13 Presidential libraries in the US in order to bring up necessity for active educational programs and suggest various possible education programs. The findings of this study can be utilized as the basic reference materials to use in the process of building and pursuing plans for educational programs of Presidential libraries or individual record centers. URL: http://ijkcdt.net/xml/00637/00637.pdf